الاحتياجات التدريبية لمعلمي أطفال ذوي التوحد المدمجين في المدارس العادية (دراسة ميدانية) - والي فطوم; جلاب مصباح; مام عواطف (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2022)
هدفت هذه الدراسة إلى معرفة الاحتياجات التدريبية لمعلمي أطفال ذوي التوحد المدمجين في المدارس العادية؛ العملية والمعرفية، والفروق في هذه الاحتياجات من حيث الجنس والمؤهل العلمي. مستخدمين المنهج الوصفي، على عينة من 15 معلما ومعلمة، خلال شهر فيفري 2020، ومن خلال تطبيقنا لمقياس "محمد أكرم حمدان"حول الاحتياجات التدريبية لمعلمي الأطفال ذوي اضطراب طيف التوحد. توصلت الدراسة إلى أن هذه الاحتياجات التدريبية عالية وأنه لا توجد فروق ذات دلالة إحصائية تعزى للمتغيرين الجنس لصالح الذكور، والمؤهل العلمي لصالح الثانوي في هذه الاحتياجات. The objectives of this study is to know the training needs(practical and cognitive) of teachers of autistic children integrated in regular schools and the differences of these needs with regard to gender and scientific levels Using the descriptive method on a sample of 15 teachers from both sexes during the month of February 2020, we applied the scale of "Mohamed Akram Hamdan" on the training needs of teachers of autistic children,. The study found that these training needs are high and that there are no statistically significant differences attributable to male sex changer, and scientific levels of benefit for secondary. in these needs.